Modeling of the collating dust process by a window air cleaner - Mikhailov, L.V.; Yersayn, R.Zh.; Mikhailova, S.L.; Ismailova, G.A.; Sokolov, A.S. (Recent Contributions to Physics, 2018)
You can use the facades of residential and administrative urban buildings to clean the city's air from ash and dust, including them in household systems and devices of smart building facades. In this case, not only the ecological task of smog control will be achieved, but economic problems with efficient use of alternative energy sources and reducing greenhouse gas emission using solar panels and energy saving technology in systems that improve comfort of the rooms as well. Since users of dust-collected devices are supposed to be natural persons, one of the tasks is requirement to develop a safe and economy-type of air cleaning. So, it is necessary to use of renewable energy flows coming to the building facades and windows which are upstream and downstream air, solar irradiation and heat flows. One of the most important tasks is to generate consumer demand for devices using the developed method of air cleaning from ash and dust. To do this, it is essential to find accompanied consumer functions that will be united in one device with an air purifier. It is shown that voltage Ue - 600 V and the battery energy costs 50J will be sufficient to charge the dust particles and prevent them from deflating air.
Keywords: dust; smog; cleaning; capture; photo electricity; light, heat; smart facade; window